Boosting Zn‐Ion Energy Storage Capability of Hierarchically Porous Carbon by Promoting Chemical Adsorption. Issue 44 (16th September 2019) - Zhang, Haozhe; Liu, Qiyu; Fang, Yuanbin; Teng, Chunlin; Liu, Xiaoqing; Fang, Pingping; Tong, Yexiang; Lu, Xihong
Abstract: The construction of advanced Zn‐ion hybrid supercapacitors (ZHSCs) with high energy density is promising but still challenging, especially at high current densities. In this work, a high‐energy and ultrastable aqueous ZHSC is demonstrated by introducing N dopants into a hierarchically porous carbon cathode for the purpose of enhancing its chemical adsorption of Zn ions. Experimental results and theoretical simulations reveal that N doping not only significantly facilitates the chemical adsorption process of Zn ions, but also greatly increases its conductivity, surface wettability, and active sites. Consequently, the as‐fabricated aqueous ZHSC based on this N‐doped porous carbon cathode displays an exceptionally high energy density of 107.3 Wh kg −1 at a high current density of 4.2 A g −1, a superb power density of 24.9 kW kg −1, and an ultralong‐term lifespan (99.7% retention after 20 000 cycles), substantially superior to state‐of‐the‐art ZHSCs. Particularly, such a cathode also leads to a quasi‐solid‐state device with satisfactory energy storage performance, delivering a remarkable energy density of 91.8 Wh kg −1 . The boosted energy storage strategy by tuning the chemical adsorption capability is also applicable to other carbon materials. Abstract : A high‐energy and ultrastable aqueous Zn‐ion hybrid supercapacitor (ZHSC) is demonstrated by introducing N dopants into a hierarchically porous carbon. N doping not only facilitates the chemical adsorption process of Zn ions, but also increases its conductivity and surface wettability. The as‐fabricated ZHSC displays a high energy density of 107.3 Wh kg −1 and an ultralong‐term lifespan.